2021
DOI: 10.1016/j.ijid.2021.06.056
|View full text |Cite
|
Sign up to set email alerts
|

Immunological predictors of disease severity in patients with COVID-19

Abstract: Background : Identifying immune cells involved in COVID-19 disease progression and predictors of poor outcomes is important to manage patients adequately. Methods : A prospective observational cohort study enrolled 53 mild non-hospitalized and 48 hospitalized confirmed COVID-19 patients to a tertiary hospital in Oman. Results : Hospitalized patients were older (58 years vs 36 years, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
2
11
1
1
Order By: Relevance
“…The mean IL-6 levels were recorded to be significantly higher in patients with severe COVID-19 compared with non-severe COVID-19 patients [15,16,[88][89][90][91][92][93][94]. Additionally, IL-6 was also reported as an independent predictor of ICU admission [95]. The results of this meta-analysis were also in line with a previous meta-analysis of RCTs that presented a reduction in the incidence of intubation in COVID-19 patients receiving IL-6 inhibitors [96].…”
Section: Discussionsupporting
confidence: 88%
“…The mean IL-6 levels were recorded to be significantly higher in patients with severe COVID-19 compared with non-severe COVID-19 patients [15,16,[88][89][90][91][92][93][94]. Additionally, IL-6 was also reported as an independent predictor of ICU admission [95]. The results of this meta-analysis were also in line with a previous meta-analysis of RCTs that presented a reduction in the incidence of intubation in COVID-19 patients receiving IL-6 inhibitors [96].…”
Section: Discussionsupporting
confidence: 88%
“…In addition, earlier studies have shown that in hospitalised patients, inflammatory biomarkers such as C-reactive protein and D-dimer can be used to predict clinical outcomes in COVID-19 patients. [ 29 , 30 ] In this study, we did not find an association between TTV load and these two serological markers.…”
Section: Discussioncontrasting
confidence: 64%
“…Indeed, the identification of laboratory predictors capable of discriminating disease severity and mortality risk will improve clinical awareness, guide interventional studies, and optimize the allocation of human and technical resources in the in-hospital management of COVID-19 ( Henry et al, 2020 ). Previous reports analyzed the routine laboratory biomarkers at hospital admission for COVID-19, suggesting that the most severe forms of COVID-19 were associated with peripheral lymphocyte and neutrophil subsets alteration ( Al Balushi et al, 2021 , Cai et al, 2021b , Lu et al, 2021 , Reusch et al, 2021 , Wang et al, 2020 ). Similarly, a wide range of metabolic parameters and biomarkers of damage, inflammatory responses, and coagulation system activation have been associated with COVID-19 poor outcomes ( Charoenngam et al, 2021 , Heer et al, 2021 , Khamis et al, 2021 , Kitakata et al, 2021 , Lv et al, 2020 , Manocha et al, 2021 , Nurlu et al, 2021 , Tang et al, 2021 )…”
Section: Introductionmentioning
confidence: 99%